2022
DOI: 10.3389/fpubh.2022.824514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Participation by Middle-Aged and Elderly Residents on the Utilization of Medical Services: Evidence From China

Abstract: ObjectivesAim to evaluate the effect of social participation on utilization of medical services among middle-aged and elderly residents in China.MethodsWe used data from the 2018 wave of the China Health and Retirement Longitudinal Study. Social participation is classified into three types. Furthermore, to control for confounding factors, our study computed propensity score matching (PSM) to evaluate the effect of social participation on the utilization of medical services.ResultThe result of PSM indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Currently, consensus on the relationship between social isolation and health service utilization among older adults has not been achieved in existing literature. Some scholars argue for a negative correlation between social isolation and health service utilization ( 23 , 25 , 36 ), aligning with the results of this study regarding family isolation. Specifically, it has been observed that socially isolated older adults exhibit lower utilization of outpatient and primary care services, but a higher likelihood of future hospitalizations and emergency room visits ( 23 , 37 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Currently, consensus on the relationship between social isolation and health service utilization among older adults has not been achieved in existing literature. Some scholars argue for a negative correlation between social isolation and health service utilization ( 23 , 25 , 36 ), aligning with the results of this study regarding family isolation. Specifically, it has been observed that socially isolated older adults exhibit lower utilization of outpatient and primary care services, but a higher likelihood of future hospitalizations and emergency room visits ( 23 , 37 ).…”
Section: Discussionsupporting
confidence: 88%
“…While existing research has investigated the link between social isolation and health service utilization, findings remain inconclusive. Some studies report that socially isolated older adults are less likely to use outpatient and home medical care services (23)(24)(25), whereas others suggest no correlation or even a positive association between social isolation and healthcare utilization (26)(27)(28)(29). Additionally, most studies inadequately assess the dimensions of social isolation, often relying on single scales or metrics to evaluate social connections and interaction frequency (30), without specifically addressing the critical types of social isolation-family, friends, and communityparticularly within the context of collectivist cultures like China's.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the medical services utilisation of middle-aged and older adults is influenced by various factors, such as age, gender, education, marriage, income and health insurance status 30 31. Thus, the following covariates were included in the analysis: age (continuous), sex (male or female), marital status (single or having a partner), religious denomination (do not belong to a denomination, Roman Catholic, Protestant, Orthodox, other Christian, Jew, Muslim, Hindu, Buddhist or other), educational level (lower, medium, upper), employment status (unemployed, full-time employed, part-time employed, self-employed, retired, housewife, students or other) and income level (comprising a total of ten steps).…”
Section: Methodsmentioning
confidence: 99%
“…Social engagement and low inpatient visits have been found to be signi cantly associated by controlling for initial health variables [20] . After controlling the effects of confounding factors, social participation signi cantly increases health services utilization among middle-aged and elderly residents in China, and different types of social activities have different degrees of in uence on the utilization of health services [21] . In addition to social participation, social networks also in uence health services utilization behavior.…”
Section: Literature Reviewmentioning
confidence: 99%